Impact Of A Pharmacist-Led Type 2 Diabetes Self-Management Education Programme Among The Community In Penang, Malaysia - Wong, Yuet Yen (2020)
Diabetes self-management education (DSME) services are not widely implemented in the current Malaysia healthcare system. Considering substantial patients with type 2 diabetes mellitus (T2DM) in Malaysia do not achieve good glycaemic control, a comprehensive DSME programme was therefore developed and tested. We employed mixed-methods to evaluate the impact of a group-based, locally developed DSME programme on participants’ biomedical (i.e. HbA1c, fasting blood glucose, blood pressure, lipid profile, body mass index, waist circumference, percentage body fat and skeletal muscle), behavioural (i.e. diet, exercise, self-monitoring of blood glucose, foot care and medication taking) and psychosocial (i.e. diabetes management knowledge, self-efficacy and quality-of-life) outcomes. Using pre-post study design, participants’ quantitative outcomes were measured at baseline, post 2-month and post 6-month of DSME. Post DSME, we interviewed selected participants to solicit in-depth perspectives towards the quality and effective components of the DSME programme. A total of 46 individuals with T2DM consented to the study. Post 2-month of DSME, participants demonstrated significant improvement in low-density lipoprotein cholesterol [3.081.04 mmol/L vs 2.630.86 mmol/L (p = 0.001)] and certain self-care behaviours including self-monitoring of blood glucose [0.921.73 vs 2.192.07 (p <0.001)] and foot care [4.541.40 vs 5.171.17 (p = 0.024)].